Educação ambiental e biodiversidade em unidades de conservação: mapeando tendências - Valenti, Mayla Willik (2010)
Protected areas (PAs) are especially interesting to develop environmental education (EE) activities, especially on biodiversity. In this study we carried out a diagnosis of the environmental education actions and biodiversity developed in protected areas and we analyzed the aspects that have influence on the tendencies of environmental education in that context. We analyze the education actions developed in Brazilian protected areas and on how 11 a public policy - the National Environmental Education Program (ProNEA) influences them using a questionnaire answered by 56 PAs. Besides, we deeply investigate the parameters of the educational practice by directly observing the visiting activities in five protected areas at São Paulo State. The questionnaires analysis showed that the environmental education developed in Brazilian protected areas present some of the principles of the new tendencies of environmental education and some principles of the public policies that have been developed in the last years in Brazil, mainly in participative management actions. Nevertheless, we have identified some distance between discourse and practice, mainly with respect to goals and carried out activities, as well as the use of monitoring and evaluation mechanisms. Similarly, we have found a great distance between theoretical and policies discourses and practice in the activities developed in the São Paulo State protected areas. On the other hand, we have identified some potentialities that could be promoted in this context: a diversity of methodological strategies and a presence of elements and situations which are favorable to improve the visitants notion of environmental issues complexity. We conclude that the elaboration and especially the implementation of specific public policies of environmental education to these areas will contribute to better explore these potentials, especially if it emphasizes the formation of the educators and the importance of using participative and dialogical methodologies, in accordance with the critical tendency of environmental education.